2007
DOI: 10.1007/s00421-007-0432-9
|View full text |Cite
|
Sign up to set email alerts
|

A re-appraisal of the reliability of the 20 m multi-stage shuttle run test

Abstract: Most studies that have set out to quantify the test-retest reliability of the multi-stage shuttle run test (MSSRT) have typically used inappropriate statistics (correlation coefficients) and/or one of two possible calculation methods for deriving predictions of maximal oxygen uptake (VO2max), and have not considered the impact of habituation on performance in the MSSRT and whether its reliability improves beyond a single repeat trial. In this context, the aim of this study was to assess the reliability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 22 publications
3
13
2
1
Order By: Relevance
“…In general, the SRT appears to be highly predictive for VO 2max (Lamb and Rogers, 2007). Although several studies have found a low correlation between the values of VO 2max determined in the SRT and those determined in laboratory tests (O’Gorman et al, 2000; St Clair Gibson et al, 1998), most studies have shown the opposite (McNaughton et al, 1998; Wilkinson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the SRT appears to be highly predictive for VO 2max (Lamb and Rogers, 2007). Although several studies have found a low correlation between the values of VO 2max determined in the SRT and those determined in laboratory tests (O’Gorman et al, 2000; St Clair Gibson et al, 1998), most studies have shown the opposite (McNaughton et al, 1998; Wilkinson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…According to Lamb and Rogers (2007), the predictive formulas developed for measuring VO 2max using the SRT are influenced by intrinsic factors such as the sample’s size, degree of heterogeneity and other dependent variables used in the regression model. In the current study, we used the predictive formula developed by Léger et al (1988), which was intended for use in populations of students, healthy adults, academic practitioners and individuals practicing sports such as basketball.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to a considerable amount of random error with repeated testing, the validity of the 20-meter shuttle run test to monitor changes in V ∙ O 2 peak has been questioned [119]. …”
Section: Exercise Tests For Indications Other Than Routine Monitoringmentioning
confidence: 99%
“…Research originally indicated that this test was a valid indicator of VO 2 max in active men and women [181, 182]. Additional research found that although the test has a strong test-retest reliability, it tends to underestimate VO 2 max when compared to a direct measure [183], with improved accuracy depending on the prediction model [184, 185]. Similar to the Chester and the Harvard step tests, this test accounts for a person’s ability to carry their own body weight, however; the MSFT can be influenced by running economy and mechanical efficiency [186], which may be crucial to moving around a ship.…”
Section: Physical Fitnessmentioning
confidence: 99%